Heparin-Induced Thrombocytopenia in Patients Suffering Cardiogenic Shock - Enzo Lüsebrink, MD; Hugo Lanz, MD; Leonhard Binzenhöfer, MD; Sabine Hoffmann, PhD; Julia Höpler, BSc; Marie Kraft, BSc; Nils Gade, MD; Jonas Gmeiner, MD; Daniel Roden, MD; Inas Saleh, MD; Christian Hagl, MD; Georg Nickenig, MD; et al. (Critical Care Explorations, 2024)
OBJECTIVES:. Cardiogenic shock (CS) is associated with high mortality. Patients treated for CS mostly require heparin therapy, which may be associated with complications such as heparin-induced thrombocytopenia (HIT). HIT represents a serious condition associated with platelet decline and increased hypercoagulability and remains a poorly researched field in intensive care medicine. Primary purpose of this study was to: 1) determine HIT prevalence in CS, 2) assess the performance of common diagnostic tests for the workup of HIT, and 3) compare outcomes in CS patients with excluded and confirmed HIT. DESIGN:. Retrospective dual-center study including adult patients 18 years old or older with diagnosed CS and suspected HIT from January 2010 to November 2022. SETTING:. Cardiac ICU at the Ludwig-Maximilians University hospital in Munich and the university hospital of Bonn. PATIENTS AND INTERVENTIONS:. In this retrospective analysis, adult patients with diagnosed CS and suspected HIT were included. Differences in baseline characteristics, mortality, neurologic and safety outcomes between patients with excluded and confirmed HIT were evaluated. MEASUREMENTS AND MAIN RESULTS:. In cases of suspected HIT, positive screening antibodies were detected in 159 of 2808 patients (5.7%). HIT was confirmed via positive functional assay in 57 of 2808 patients, corresponding to a prevalence rate of 2.0%. The positive predictive value for anti-platelet factor 4/heparin screening antibodies was 35.8%. Total in-hospital mortality (58.8% vs. 57.9%; p > 0.999), 1-month mortality (47.1% vs. 43.9%; p = 0.781), and 12-month mortality (58.8% vs. 59.6%; p > 0.999) were similar between patients with excluded and confirmed HIT, respectively. Furthermore, no significant difference in neurologic outcome among survivors was found between groups (Cerebral Performance Category [CPC] score 1: 8.8% vs. 8.8%; p > 0.999 and CPC 2: 7.8% vs. 12.3%; p = 0.485). CONCLUSIONS:. HIT was a rare complication in CS patients treated with unfractionated heparin and was not associated with increased mortality. Also, HIT confirmation was not associated with worse neurologic outcome in survivors. Future studies should aim at developing more precise, standardized, and cost-effective strategies to diagnose HIT and prevent complications.